Psychological Capital on Working Generation: The Role of Hope, Self-Efficacy, and Resilience on Self-Perceived Employability in University Students - Helin Trialia Febrianti; Dian Febriany Putri (LPPM Universitas 17 Agustus 1945 Samarinda, 2026)
The dominance of the number of private universities in Indonesia does not guarantee that private universities stand out in terms of quality compared to public universities. Final year students need to prepare themselves by increasing their psychological capital to compete in the labour market to reduce the phenomenon of unemployment of undergraduate graduates in Indonesia. The quantitative research method with a correlational research design in this study was used to analyze the role of psychological capital, consisting of the dimensions of hope, optimism, self-efficacy, and resilience, on self-perceived employability in final year students at private universities. Participants were selected based on predetermined criteria, namely undergraduate students at least currently in semester 8 at private universities with a total of 205 participants. The Student Self-Perceived Employability Scale and The Compound Psychological Capital Scale were adapted into Indonesian so that it could be used in this study. Based on multiple linear regression analysis, the results showed that hope, self-efficacy, and resilience positively and significantly predicted self-perceived employability among final-year students at private universities, while optimism did not show a significant effect. These findings highlight the importance of fostering psychological capital through both individual effort and institutional support. Collaborative programs between universities, industries, and related institutions that nurture students’ hope, self-efficacy, resilience, goal setting, and perseverance can further strengthen their employability and readiness to thrive in the dynamic labor market.